To the Anishinaabeg of the Future - Smiles, Niiyokamigaabaw Deondre (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
A letter written to future generations of Anishinaabeg expressing my desires for what they can accomplish, and how we can help them get there.